DIFFERENT ASPECTS OF TRADITIONAL AND ISLAMIC BANKING SYSTEMS IN MODERN FINANCIAL RELATIONS - Bektemirov, Abdukhamid; Gadoev, Bekzod (Innovative Development in Educational Activities, 2024)
The article analyzes the features and characteristics of the Islamic banking system, which is widely popular today, compared to traditional commercial banks, and examines its importance in economic development.